The Effect of Learning Model Multimedia-Based toward The Students’ English Ability at Senior High School of Kolaka Regency - Kadaruddin Kadaruddin (STKIP Singkawang, 2017)
This research was design to know the effect of learning model multimedia-based toward the students’ English ablility at senior high school of Kolaka Regency. The question of the research was “Is there an effect of learning model multimedia-based toward the students’ English ablility at senior high school of Kolaka Regency? The objective of the research was to find out the data whether the learning model multimedia-based has an effect toward the students’ English ablility at senior high school of Kolaka Regency. The significant of the research was expected the model can be used as reference learning model to improve the students’ English ablility. The design of the research was pre-experimental design. The research was conducted at the first-class students of Senior High School 1 Wundulako in Kolaka District. The data were collected by using English test which given at the pre-test and the post-test. In analysed the students’ test result, which the mean score of pre-test was 33,8806 and the mean score of post-test was 69,4058, while the t-table 18,55>2,042 t-test. Its mean that the learning model multimedia-based has an effect toward the students’ English ablility. Refering to the findings and discussions of the research, it can be concluded that the learning model multimedia-based has an effect toward the students’ English ablility at senior high school of Kolaka Regency. It was based on the mean score in pre-test and post-test.Based on the conclusion of the research, the researcher suggests to the teacher, especially English teacher in Kolaka Regency to use learning model multimedia-based in teaching and learning process to improve the students’ English ability.